Sosialisasi Meningkatkan Pemahaman Penyusunan dan Partisipasi Masyarakat Dalam Pembentukan Peraturan Desa - Rommy Patra; Chandra Maharani; Deden Kurnia; Astri Kusumadela; Daichi Putri Karamigi; Iskandar Iskandar (Pusat Riset dan Inovasi Nasional, 2025)
Community participation in the formation of Village Regulations (Perdes) is an important indicator in realizing transparent, democratic, and responsive village governance to the needs of residents. However, in Teluk Kapuas Village, the level of community participation in the process is still relatively low. This is evident from the minimal involvement of residents and village officials in understanding the mechanisms and urgency of Perdes preparation. Based on these conditions, Community Service (PKM) activities were carried out with the aim of increasing the knowledge, understanding, and awareness of the community and village officials regarding the importance of active involvement in Perdes formation. The problems raised in this activity include: (1) the level of knowledge and understanding of village officials regarding the procedures for Perdes formation; and (2) factors that hinder the community from participating optimally. The methods used were lectures and interactive discussions involving village officials and community representatives. The results of the activities showed that the understanding of village officials and the community was still limited, so that participation in Perdes formation was not optimal. Through this PKM activity, it is hoped that there will be an increase in the understanding, awareness, and involvement of the Teluk Kapuas Village community in the Perdes formulation process so that it can produce village regulations that are more participatory and meet the needs of residents.